Tensile force measurement by using different lingual retainer wires, bonding materials types and thickness (A comparative in vitro study) - Yassameen A Salih; Mushriq F Al-Janabi (College of Dentistry/ University of Baghdad, 2014)
Background: The bonded orthodontic retainer constructed from multistrand wire and composite is an efficient esthetic retainer, which can be maintained long-term. Clinical failures of bonded orthodontic retainers, most commonly at the wire/composite interface, have been reported. This in vitro investigation aimed to evaluate the tensile forces of selected multistrand wires and composite materials that are available for use in the construction of bonded fixed retainers. Materials and Methods: The study sample includes 120 wires with three types of retainer wires (3 braided strands\ Orthotechnology, 8 braided strands\ G&H Orthodontics, 6 coaxial strands\ Orthoclassic wires), two types of adhesive (flowable\ Orthotechnology, non flowable\ G&H Orthodontics composites) and two thickness of the adhesive (1mm, 2mm). The samples were prepared for each composite in which a wire was embedded; then the composite was light cured for 40 seconds and the specimens were stored in artificial saliva at 37°C in the incubator for 24 hours. The ends of the wire were drawn up and tensile force was applied through Tinius-Olsen universal testing machine until the resin failed and the results were recorded in Newton (N). Results: Statistical analysis showed that there was a highly significant difference (P ≤ 0.01) among the mean values of tensile forces of the three types of retainer wires in each thickness of composite with exception of a non significant difference (P > 0.05) between (3 braided) and (8 braided) and a non significant difference (P > 0.05) between (3 braided) and (6 coaxial) in both thickness of composite, a highly significant difference (P ≤ 0.01) between the two thickness of both composite types in each wire type and a highly significant difference (P ≤ 0.01) between the two types of composite in each wire type of both thickness of composite. Conclusion: The result of this study revealed that the 8 braided strands retainer wire shows the highest values of tensile force among the tested retainer wires, the non flowable composite demonstrates a higher tensile force than the flowable composite and increasing the thickness of composite overlying the wire increased the force required to detach the wire from the composite.